How economic contexts shape calculations of yield in biodiversity offsetting. Issue 5 (6th September 2017) - Carver, L.; Sullivan, S.
Abstract: We examined and analyzed methods used to create numerical equivalence between sites affected by development and proposed conservation offset sites. Application of biodiversity offsetting metrics in development impact and mitigation assessments is thought to standardize biodiversity conservation outcomes, sometimes termed yield by those conducting these calculations. The youth of biodiversity offsetting in application, however, means little is known about how biodiversity valuations and offset contracts between development and offset sites are agreed on in practice or about long‐term conservation outcomes. We examined how sites were made commensurable and how biodiversity gains or yields were calculated and negotiated for a specific offset contract in a government‐led pilot study of biodiversity offsets in England. Over 24 months, we conducted participant observations of various stages in the negotiation of offset contracts through repeated visits to 3 (anonymized) biodiversity offset contract sites. We conducted 50 semistructured interviews of stakeholders in regional and local government, the private sector, and civil society. We used a qualitative data analysis software program (DEDOOSE) to textually analyze interview transcriptions. We also compared successive iterations of biodiversity‐offsetting calculation spreadsheets and planning documents. A particular focus was the different iterations of a specific biodiversity impact assessment in which the biodiversity offsetting metric developed by the U.K.'s Department for Environment, Food and Rural Affairs was used. We highlight 3 main findings. First, biodiversity offsetting metrics were amended in creative ways as users adapted inputs to metric calculations to balance and negotiate conflicting requirements. Second, the practice of making different habitats equivalent to each other through the application of biodiversity offsetting metrics resulted in commensuration outcomes that may not provide projected conservation gains. Third, the pressure of creating value for money diminished projected conservation yields.